Juvenile Recurrent Parotitis: A Case Report - Jalal, Muhammed Jasim Abdul; Pittappilly, Babu Mathew; Kandathil, Julio Chacko (Journal of Pediatric Infectious Diseases, 2019)
Juvenile recurrent parotitis (JRP) is defined as recurrent inflammatory parotitis in children of unknown etiology. It is described as recurrent parotid inflammation, usually associated with non-obstructive sialectasis of peripheral ducts of the parotids with periductal lymphocytic infiltration of the parotid gland. It is characterized by multiple episodes of parotid swelling and/or pain associated with fever or malaise over a period of years. Symptoms resolve spontaneously after puberty. All children with recurrent parotitis should be screened to exclude Sjögren's syndrome, lymphoma, and immunodeficiency including human immunodeficiency virus. We present the case of a 4-year-old boy who had four episodes of recurrent parotid swelling over a period of 6 months.
Keywords: recurrent parotitis; sialectasis; sialography; sialendoscopy